Students’ Perception of Autonomous Learning Activities - Firman Khaidir; Friscilla Wulan Tersta; Rengki Afria (UIR Press, 2020)
Autonomous learning activity is an approach and process in which individual take responsibility for their learning. The method of this research is quantitative, sample took in Senior High School 1 Ma. Jambi. This study is aimed to investigate the students’ perception of their autonomous learning activities. The results of this study show that, in general, students’ learning autonomy is still in the medium level, but in details, in some particular aspects, it is at the low level. Significances arising from this study are: knowing students’ perception of their learning autonomy is able to assist EFL teachers, material and curriculum developers, and administrators to construct supporting programs and materials to foster students’ learning autonomy. Besides, by conducting such research, it can significantly contribute the ideas of how learning autonomy in EFL context is encouraged. English as a foreign language in Indonesia and its magnitude in this globalization era urgently needs to have more exposure in term of opportunities in autonomous activities, so that students’ awareness of their learning responsibility is achieved.